Sea ice variability in the southern Norwegian Sea during glacial Dansgaard-Oeschger climate cycles - Sadatzki, Henrik; Dokken, Trond Martin; Berben, Sarah Miche Patricia; Muschitiello, Francesco; Stein, Ruediger; Fahl, Kirsten; Menviel, Laurie; Timmermann, Axel; Jansen, Eystein (Science Advances, 2020)
The last glacial period was marked by pronounced millennial-scale variability in ocean circulation and global climate. Shifts in sea ice cover within the Nordic Seas are believed to have amplified the glacial climate variability in northern high latitudes and contributed to abrupt, high-amplitude temperature changes over Greenland. We present unprecedented empirical evidence that resolves the nature, timing, and role of sea ice fluctuations for abrupt ocean and climate change 32 to 40 thousand years ago, using biomarker sea ice reconstructions from the southern Norwegian Sea. Our results document that initial sea ice reductions at the core site preceded the major reinvigoration of convective deep-water formation in the Nordic Seas and abrupt Greenland warming; sea ice expansions preceded the buildup of a deep oceanic heat reservoir. Our findings suggest that the sea ice variability shaped regime shifts between surface stratification and deep convection in the Nordic Seas during abrupt climate changes. publishedVersion